(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the pattern of dermatological diseases at Bach Mai Hospital. Methods: A retrospective cross-sectional study was conducted on 32,083 dermatology visits at the Dermatology Clinics of the Outpatient Department, Bach Mai Hospital, in 2024. Data were analyzed using Stata 15.0; the Chi-square test was applied with a statistical significance level of p < 0.05. Results: 53.8% of visits were by female patients and 37.0% by patients aged 20–39 years. The three most frequent diagnoses were atopic dermatitis/eczema (11.7%), tinea (10.2%), and glossitis/stomatitis (8.3%). Sex differences were statistically significant for 13 of 15 disease groups (p < 0.001): sexually transmitted infections, scabies, and psoriasis were more frequent among visits by male patients, whereas autoimmune connective tissue diseases (SLE, systemic sclerosis), alopecia, glossitis/stomatitis, and herpes zoster were more frequent among visits by female patients. Visits were concentrated in summer (30.2%) and autumn (29.1%). Conclusion: The pattern of the 15 most common dermatological disease groups showed differences by sex and season. These findings support the need to allocate resources and design medical interventions according to disease group, sex, and time of year.